2020
DOI: 10.1016/j.annonc.2020.08.1254
|View full text |Cite
|
Sign up to set email alerts
|

1131P C-reactive protein as biomarker for immune-related adverse events in melanoma patients treated with immune checkpoint inhibitors in the adjuvant setting

Abstract: Background: Inherited pathogenic variants (PV) in the CDKN2A tumour suppressor gene are among the strongest known risk factors for cutaneous melanoma. CDKN2A encodes for the cell cycle inhibitors p16 ink4 and p14ARF, and dysregulation of the p16/RB1 pathway is a well-known mechanism of resistance to MAPK-directed targeted therapy due to the interplay between the two pathways. For this reason, we wondered whether patients with germline CDKN2A PVs may achieve suboptimal results with BRAF and MEK inhibitors.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Laboratory analyses are helpful in differential diagnosis of other coexisting organ toxicities of immunotherapy. Immunological pneumonitis is associated with a moderate increase in C-reactive protein (CRP) concentration, and a decrease in CRP concentration correlates with response to treatment [25]. Therefore, additional laboratory tests (e.g., determining procalcitonin concentrations in serum) or bacteriological and virological analyses may be necessary to differentiate IP and pneumonia caused by an infectious agent.…”
Section: Bacteriological Testsmentioning
confidence: 99%
“…Laboratory analyses are helpful in differential diagnosis of other coexisting organ toxicities of immunotherapy. Immunological pneumonitis is associated with a moderate increase in C-reactive protein (CRP) concentration, and a decrease in CRP concentration correlates with response to treatment [25]. Therefore, additional laboratory tests (e.g., determining procalcitonin concentrations in serum) or bacteriological and virological analyses may be necessary to differentiate IP and pneumonia caused by an infectious agent.…”
Section: Bacteriological Testsmentioning
confidence: 99%
“…Another very interesting field of research is the investigation of predictive markers in terms of drug-related adverse events. In a recent study, Lauwyck and colleagues [ 59 ] found how C-reactive protein (CRP) may be of use in predicting immune-related adverse events (irAE) related to adjuvant treatment with immune checkpoint inhibitors. Through retrospective analysis of 72 melanoma patients, they observed how in patients that experience irAE, the median serum CRP-levels exceeded the ULN (5 mg/L).…”
Section: Protein Expressionmentioning
confidence: 99%